We who are not as others: análise de noções da violência no mosh a partir do heavy metal - Lucia Vulcano de Andrada (2013)
This research aims to promote a discussion about notions of violence in the mosh - a type of dance that happens through punches, kicks and shoves. From ethnographic data, testimonies and experiences of people who practice mosh, it was observed that the violence experienced in this type of dance happens in different conditions, where there is a set of rules and structures shared among the participants of a mosh. Considering this event from the text "A Arqueologia da Violência" of Pierre Clastres, this research aims to deconstruct the notion of violence as something that is built as a deviant behavior, offering new significance to it as a shared value in a culture where it emphasizes courage and aggressiveness.